Device characterization of organic nanostructure based on sodium copper chlorophyllin (SCC) - Aydin, M. E.; Farag, A. A. M.; Abdel-Rafea, M.; Ammar, A. H.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2012)
Thin films of nanocrystalline sodium copper chlorophyllin, SCC were prepared by spin coating technique at room temperature (300 K). The films were identified by scanning electron microscopy (SEM), particle size analyzer (PSA) and X-ray diffraction (XRD). The energy band model was applied and the type of the optical transitions responsible for optical absorption was found to be direct allowed transition. Devices of Al/SCC/ITO were fabricated and the current density-voltage measurements showed diode characteristics. The photovoltaic parameters were calculated from the J-V characteristics under illumination through ITO and discussed in detail. Some junction parameters of the device such as ideality factor, barrier height, and series resistance were determined from J-V and C-V characteristics. The obtained ideality factor of the device shows non-ideal diode characteristics with the value of ideality factor greater than unity. This indicates the recombination process of electron-hole in the depletion region. The diffusion potential determined from the linear region of the J-V characteristics is found to be in close with that obtained from C-V measurements at 1 MHz. A space charge limited conduction (SCLC) controlled by an exponential distribution of traps above the valence band edge was observed at higher voltage region. The interface state density (N-ss) was determined as a function of energy separation from the valence-band edge. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Sodium copper chlorophyllin; Thin films; Nanocrystalline; Optical properties; Photovoltaic properties